2015
DOI: 10.1039/c5fd00011d
|View full text |Cite
|
Sign up to set email alerts
|

Electrode kinetics of the NiO porous electrode for oxygen production in the molten carbonate electrolysis cell (MCEC)

Abstract: The performance of a molten carbonate electrolysis cell (MCEC) is to a great extent determined by the anode, i.e. the oxygen production reaction at the porous NiO electrode. In this study, stationary polarization curves for the NiO electrode were measured under varying gas compositions and temperatures. The exchange current densities were calculated numerically from the slopes at low overpotential. Positive dependency on the exchange current density was found for the partial pressure of oxygen. When the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Though the kinetics of CO 2 electrolysis is slower than water splitting, CO could be produced through the CO 2 reduction (Equation 28). At the anode, CO 3 2− ions oxidize, generating CO 2 and O 2 (Equation 29) [217].…”
Section: High-temperature Electrolysis Cellsmentioning
confidence: 99%
“…Though the kinetics of CO 2 electrolysis is slower than water splitting, CO could be produced through the CO 2 reduction (Equation 28). At the anode, CO 3 2− ions oxidize, generating CO 2 and O 2 (Equation 29) [217].…”
Section: High-temperature Electrolysis Cellsmentioning
confidence: 99%
“…Their results indicate that in the temperature range 600-675 • C the overall MCFC performance in electrolysis mode is slightly better than in fuel cell operation mode (Hu et al, 2014), which could open on the possibility of using conventional MCFC electrodes as efficient bi-functional electrode catalysts. Lower polarization losses of the porous NiO oxygen electrode were identified as the main cause for the better performance in electrolysis mode (Hu et al, 2014(Hu et al, , 2015b. In particular, it was found that gas production at the NiO oxygen electrode [reaction (2)] takes place under a dominant charge transfer control (Hu et al, 2015b), being the role of mass transfer polarization negligible even at higher current densities, which is a striking difference as compared to a MCFC running in the conventional fuel cell mode.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because MCFC consume CO 2 at the cathode side and release CO 2 at the anode side, they have been proposed to combine this electricity production capability with the capture and the concentration of CO 2 out of exhaust gas from steel mills [3][4][5]. Alternatively, the high solubility of CO 2 in molten carbonates is a possible path to perform carbon capture and utilization (CCU) by electroreduction of CO 2 in molten carbonate electrolyser cells (MCEC) [6][7][8][9][10]. The reduction of CO 2 in MCEC into amorphous carbon has been well documented and the conversion of CO 2 to CO or even CH 4 has also been evidenced recently [11][12][13], thus adding another opportunity for carbon capture and utilisation using carbonate melts.…”
Section: Introductionmentioning
confidence: 99%